Analisa Kelayakan Tarif Kereta Api Ekonomi Lokal Rute Sidoarjo - Bojonegoro dengan Metode Willingness to Pay - Syafrial Burhany; Nugroho Utomo; Ibnu Sholichin (Jurnal Syntax Admiration, 2023)
Feasibility Analysis of Local Economy Train Fares for Sidoarjo - Bojonegoro Route with Willingness To Pay Method. This study aims to determine the fare that is in accordance with the Local Economy Train service on the Sidoarjo - Bojonegoro route. The demand for train travel between the two cities is high due to the high economic potential and individual mobility in Sidoarjo and Bojonegoro regencies. However, the Local Economy Train service is still not optimal with air conditioning problems, long travel routes, and uncomfortable seating facilities. The willingness to pay method was used in this study by considering passenger load factors, distance fares, and passenger satisfaction. The evaluation was carried out quantitatively and qualitatively on the services and fares of the Local Economy Train for the Sidoarjo - Bojonegoro route. The load factor in 2021 reached 74.83%, exceeding the load factor standard of 70%. Factors that affect people's willingness to pay rates include punctuality, information, schedules, rates, facilities, service quality, cleanliness, security, and safety. The respondents' assessment shows that the facilities and services of the Local Economy Railway are good. The value of willingness to pay on a trip with a fare of IDR 6,000 is IDR 7,219.44, while with a fare of IDR 12,000 it reaches IDR 12,321.2. The trip fare is based on operational costs of Rp 10,773 for a distance of 133 km. This research is expected to help PT. KCI improves services and determines the appropriate fare for the Local Economy Train service on the Sidoarjo - Bojonegoro route.